Critical Analysis in Developing System Application And Product (SAP) and Internal Control - Rehuel, Kevin (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This research is a critical analysis of the Accounting Information System (AIS) and its impact on internal control weaknesses. Although computer-based AIS offers significant advantages in speed, accuracy, and data processing efficiency, implementation can be complex and incur high costs for procurement of hardware, software, and ongoing maintenance. This research uses a case study from PT. BGA, where the subsidiary experienced inventory theft. During the centralized inventory process, significant discrepancies were discovered in the subsidiary's warehouse, resulting in huge losses for the parent company. Critical analysis reveals the weaknesses that exist in PT. BGA. The company uses a fragmented system, with SAP applications not yet fully implemented across all departments. Accounting data is still managed through additional applications such as MS Excel and transferred via email, creating potential gaps in data retrieval and consolidation in the SAP system. This fragmented approach increases the risk of incomplete or inaccurate data reaching headquarters for processing, ultimately contributing to undetected theft. This case study emphasizes the importance of comprehensive and integrated AIS. Implementing SAP across an organization will likely facilitate real-time data visibility and improve internal controls, thereby preventing inventory theft.